A critical role of a plant-specific TFIIB-related protein, BRP1, in salicylic acid-mediated immune response - Xu, Binjie; Fan, Baofang; Chen, Zhixiang (Frontiers in Plant Science, 2024)
An integral part of plant immunity is transcription reprogramming by concerted action of specific transcription factors that activate or repress genes through recruitment or release of RNA polymerase II (Pol II). Pol II is assembled into Pol II holoenzyme at the promoters through association with a group of general transcription factors including transcription factor IIB (TFIIB) to activate transcription. Unlike other eukaryotic organisms, plants have a large family of TFIIB-related proteins with 15 members in Arabidopsis including several plant-specific TFIIB-related proteins (BRPs). Molecular genetic analysis has revealed important roles of some BRPs in plant reproductive processes. In this study, we report that Arabidopsis knockout mutants for BRP1, the founding member of the BRP protein family, were normal in growth and development, but were hypersusceptible to the bacterial pathogen Psuedomonas syringae. The enhanced susceptibility of the brp1 mutants was associated with reduced expression of salicylic acid (SA) biosynthetic gene ISOCHORISMATE SYNTHASE 1 (ICS1) and SA-responsive PATHOGENESIS-RELATED (PR) genes. Pathogen-induced SA accumulation was reduced in the brp1 mutants and exogenous SA rescued the brp1 mutants for resistance to the bacterial pathogen. In uninfected plants, BRP1 was primarily associated with the plastids but pathogen infection induced its accumulation in the nucleus. BRP1 acted as a transcription activator in plant cells and binded to the promoter of ICS1. These results collectively indicate that BRP1 is a functionally specialized transcription factor that increasingly accumulates in the nucleus in response to pathogen infection to promote defense gene expression.